Survey on factors influencing surgeons' sensation in Polish operating theatres. (15th April 2022) - Ćwiklińska, Dominika; Bogdan, Anna; Szyłak-Szydłowski, Mirosław
Abstract: Operating theatres are very demanding environments that should provide a safe and comfortable indoor environment for the patient and medical staff and, above all, minimize the risk of cross-infection among patients. Patient safety and health are a priority, and these factors are impacted by surgeons. The present study aimed to analyse surgeons' perceptions of the indoor environment in Polish operating rooms, including the acceptability of the conditions and their perceptions of workload capacity. The results of our study demonstrate that 86.1% of physicians found the thermal environment uncomfortable, 62.7% found the noise in the operating room uncomfortable, and 62.7% found the lighting in operating rooms uncomfortable. During the procedure, for 69.7% of respondents, the smell in the operating room was perceptible, but for 70.3%, it was acceptable. The greatest discomfort associated with clothing is its impermeability, which leads to discomfort in an overly warm environment. The study showed that the environment of operating rooms is very important due to the confirmed difficulties in Polish operating rooms and that the scope of research should be broadened to improve the environmental conditions, which will reduce the difficulty of work for medical staff. Highlights: The study analysed surgeons' perception of the environment in operating rooms. The thermal environment was most often perceived as uncomfortable. The noise for over 60% of surgeons was an annoyance in operating rooms. Odour was most often accepted by the doctors. For 51% of surgeons the lighting in the operating room was unacceptable.